Pengaruh Pengeluaran Pemerintah Dalam Bidang Pendidikan Dan Kesehatan Terhadap Indeks Pembangunan Manusia - Dhae, Firgelius; Renggo, Yuniarti Reny; Hudang, Adrianus Kabubu (Universitas Kristen Wira Wacana Sumba, 2025)
This study aims to analyze the effect of government spending in education and health on increasing the Human Development Index (HDI) in East Nusa Tenggara Province. Using panel data from several regencies/cities during the period 2017-2023, this study applies an econometric model to evaluate the contribution of government spending in education and health to the HDI, which includes dimensions of health, education, and standard of living. The results of the analysis show that increasing government spending in the education and health sectors significantly affects the increase in the HDI. This study also identifies the important role of efficient government budget allocation in supporting more equitable human development. These findings indicate that fiscal policies that focus on education and health can be the key to improving the quality of life and human development in NTT Province.